2020
DOI: 10.1051/0004-6361/202038022
|View full text |Cite
|
Sign up to set email alerts
|

Stellar coronal X-ray emission and surface magnetic flux

Abstract: Context. Observations show that the coronal X-ray emission of the Sun and other stars depends on the surface magnetic field. Aims. Using power-law scaling relations between different physical parameters, we aim to build an analytical model to connect the observed X-ray emission to the surface magnetic flux. Methods. The basis for our model are the scaling laws of Rosner, Tucker & Vaiana (RTV) that connect the temperature and pressure of a coronal loop to its length and energy input. To estimate the energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 41 publications
7
29
0
Order By: Relevance
“…In our analytical study, we found the power-law index m to be in the range from roughly one to almost two (Zhuleku et al 2020). This result agrees relatively well with most observations, but at least one more recent observation finds an even steeper power-law connection of L X ∝ Φ m with m of 2.68 (Kochukhov et al 2020).…”
Section: Analytical Scaling Relationssupporting
confidence: 90%
See 4 more Smart Citations
“…In our analytical study, we found the power-law index m to be in the range from roughly one to almost two (Zhuleku et al 2020). This result agrees relatively well with most observations, but at least one more recent observation finds an even steeper power-law connection of L X ∝ Φ m with m of 2.68 (Kochukhov et al 2020).…”
Section: Analytical Scaling Relationssupporting
confidence: 90%
“…We found that the temperature response function for temperatures below log 10 T [K] = 7 can be expressed as a power law (cf. Zhuleku et al 2020, their Fig. 1), R ∝ T α .…”
Section: Analytical Scaling Relationsmentioning
confidence: 90%
See 3 more Smart Citations